Analisis Persepsi Bisnis Terhadap Persepsi Konsumen Melalui Indeks Tendensi Bisnis (ITB) dan Indeks Tendensi Konsumen (ITK) di Indonesia. - Agung Gatra Diarga (Cendekia Niaga, 2020)
The condition of the global economy is greatly affected by the movements of economic agents itself. After the global crisis that happened years ago, 2018 the state of the global economy not fully recovered. In the moment the role of economic agents so influenced by the information received and how that information is processed, so that will affect the perception on an object of that information. And in the end will have an impact on decision making right or not. In this research will analyze perception on the impact of business to consumer perception shown through indicators of the business tendency index on consumer tendency index. The research was conducted using secondary data from the central bureau of statistics by focusing on a span of years the global crisis that is 2017-2019 or pre until post crisis. The method used is descriptive statistics analysis. The result of which is known that the perception business have a positive influence on consumer perception in the view through the business tendency index on consumer tendency index